Aplicação de silício no solo e resistência de híbridos de milho a larvas de Diabrotica speciosa (Coleoptera: Chrysomelidae) - Maciel, Jean Rafael da Cruz (2018)
Brazil is the third largest producer of corn in the world. The high yield obtained in maize is a result good plant development during the crop cycle, supported by good water availability in the soil and best management practices, resulting in effective plant nutrition and control of insect pests and diseases. Diabrotica speciosa stands out as an important insect species causing significant damage to the plant roots consequently reducing the absorption of water and nutrients. It is reported as key corn pest in Brazilian southern states and some areas of the Southeast and Center-West. Its impacts might cause yield losses ranging from 10 to 13% under high infestation. Some methods of control might be used to reduce pest infestation and consequently the damage caused by the insect such as chemical control, transgenic plants and biological control. An alternative potential method could be to induce plant resistance with silicon (Si) through plant nutrition. Studies have shown that Si can stimulate plant growth and yield, as well as confer protection against abiotic factors, such as aluminum toxicity and water scarcity, and against biotic stress such as diseases and insects. Therefore, the hypothesis of this work is that Si also promotes modifications in the anatomy and morphological characteristics of the root system leading to an increased resistance against D. speciosa in maize plants. The project was conducted under greenhouse conditions, in a 2x2x2 factorial scheme: two maize hybrids, two quantities of silicon and two degrees of infestation by D. speciosa (with and without infestation). The attributes plant height, dry mass (root and above ground), Si content (root and above ground), root injury caused by the insect and anatomical characters of the root system were measured and submitted to analysis of variance and to the comparison test of means of Tukey to 5%. The higher availability of Si did not impact the plant biomass production (root and above ground). Si can induce modifications in the anatomy of the root system. By the other hand differences were found between maize hybrids. The HY01 hybrid showed a natural higher degree of resistance to D. speciosa larvae, potentially conferred by better root development and higher deposition of suberin in the exoderm, since this compound stimulates defense enzymes against herbivory. Based on these results, we conclude that under these tested conditions the application of Si did not promote resistance to D. speciosa larvae